An Inductive Link-Based Wireless Power Transfer System for Biomedical Applications - M. A. Adeeb; A. B. Islam; M. R. Haider; F. S. Tulip; M. N. Ericson; S. K. Islam (Active and Passive Electronic Components)
A wireless power transfer system using an inductive link has been demonstrated for implantable sensor applications. The system is composed of two primary blocks: an inductive power transfer unit and a backward data communication unit. The inductive link performs two functions: coupling the required power from a wireless power supply system enabling battery-less, long-term implant operation and providing a backward data transmission path. The backward data communication unit transmits the data to an outside reader using FSK modulation scheme via the inductive link. To demonstrate the operation of the inductive link, a board-level design has been implemented with high link efficiency. Test results from a fabricated sensor system, composed of a hybrid implementation of custom-integrated circuits and board-level discrete components, are presented demonstrating power transmission of 125 mW with a 12.5% power link transmission efficiency. Simultaneous backward data communication involving a digital pulse rate of up to 10 kbps was also observed.